The role of the media in the rise of violence and rioting in Algerian football stadiums - mhimdat, rachid; hamrouche, ahmed ridha; قريون, خالد (sports creativity, 2025)
Football is one of the sports that has captivated audiences since its inception. However, history reveals that this sport has not always been a bed of roses, nor adorned with joys. It has witnessed many setbacks and tragedies that are truly shameful. Perhaps one of the most influential elements surrounding football is the media, which is the focus of this study. Using a descriptive methodology and interviews as a data collection tool, statistically, it became clear that specialized print media plays a prominent role in the rise of violence, while non-specialized media, unlike radio and television, contribute to this to a lesser extent. These findings call for a more judicious approach to what is written and reaches readers, whether they are fans or not, in order to help mitigate the dangers of this phenomenon, which has been and continues to be detrimental to the principles of football.